Pengaruh Profitabilitas, Leverage dan Ukuran Perusahaan Terhadap Pengungkapan Islamic Social Reporting dengan Dewan Pengawas Syariah Sebagai Variabel Moderasi (Studi Empiris pada Bank Umum Syariah di Indonesia) - Murliani Musa; Muhammad Wahyuddin Abdullah; Abdul Wahid Haddade (Jurnal Iqtisaduna, 2023)
This study aims to determine the effect of profitability, leverage and company size on the disclosure of Islamic Social Reporting. This research is a quantitative research with a causal approach. Purposive sampling method as many as 13 Islamic Commercial Banks in Indonesia. Multiple linear regression analysis for the hypothesis of profitability, leverage and firm size on disclosure of Islamic Social Reporting. And analysis of regression moderation with the absolute difference value approach for the hypothesis of profitability, leverage and company size on disclosure of Islamic Social Reporting which is moderated by the sharia supervisory board. The results of the study with multiple linear regression analysis show that profitability, leverage and firm size have a positive effect on disclosure of Islamic Social Reporting. Analysis of the moderating variable with the absolute difference value approach shows that the sharia supervisory board is able to strengthen the influence of profitability, leverage and company size on disclosure of Islamic Social Reporting.